Shelf humic substances as carriers for basin-scale iron transport in the North Pacific - Yamashita, Youhei (Sci Rep, 2020)
Iron is one of the key elements controlling phytoplankton growth in large areas of the global ocean. Aeolian dust has traditionally been considered the major external source of iron in the North Pacific. Recent studies have indicated that sedimentary iron from the shelf region of the Sea of Okhotsk has a strong impact on the iron distribution in the North Pacific, while the mechanism supporting its long-distance transport remains poorly understood. Here, we report that refractory shelf humic substances, which complex and carry dissolved iron, are transported conservatively at least 4000 km from the shallow sediments of the Sea of Okhotsk to the subtropical North Pacific with the circulation of intermediate water. This result indicates that shelf humic substances are probably one of the key factors shaping the distribution of dissolved iron in the ocean interior.